Detecção de Sclerotinia sclerotiorum em meio Neon-S modificado em sementes de soja e feijão - Santos, Roberto Resende dos (2015)
The Neon-S method has been used for the detection of Sclerotinia sclerotiorum in soybean and common beans since the agricultural year 2010. However, this method yields false positive readings due to other fungi that change medium pH. Thus, this study evaluated the contribution of increasing incubation period on the optimization of Neon-S reliability in different cultivars of soybeans and common beans. Nine treatments were evaluated in randomized blocks design, as a 3x3 factorial, with three replications. The factors were three detection methods (paper roll, Neon- S, and Neon S2) and three cultivars: naturally infected Pérola beans; naturally infected soybean cultivar BRS Valiosa RR, and artificially inoculated soybean cultivar Nidera 7255 RR). Inoculation of soybean Nidera 7255 RR was done by incubating the seeds for 72 h on PDA where the fungus was previously grown for seven days at 25 ºC. The three methods were compared, evaluating 400 seeds per replication, after incubation for seven days in Neon-S, for 15 days in Neon-S2, and for 30 days in paper roll, determining the presence of the fungus, and that of sclerotia adhered to the seeds. Twenty seeds were used per plate for media Neon-S and Neon-S2 (20 plates per replication), and 50 seeds per roll for the paper roll. Seeds were incubated at 20 ºC in BDO chamber in darkness. The data were submitted to the analysis of variance and the averages compared by the Tukey test at 5% probability. The interaction between detection method and cultivar was significant at 1% probability, indicating that the best method depends on the cultivar under study. Among the cultivars evaluated, artificially infected soybean presented the greatest indices of pathogen infection. A comparison of seed lots analyzed at the Plant Disease Clinic LAMIP proved greater sensibility of Neon-S in a total of 637 lots evaluated from 2008 to 2012. In that period, the paper roll test resulted in 21.88% positive samples, while in Neon-S 31.25% of them were positive. Another distinguishing factor among the lots analyzed was the percentage of infected and, or, contaminated seeds, which varied from one (0.25%) to five (1.25%). Therefore, detection of S. sclerotiorum by the Neon-S2 method can be optimized by incubation for 15 days, considering that, in this case, the formation of sclerotia near the infected seeds confirm the presence of the pathogen, avoiding false positive readings. Neon-S2 method increased detection sensibility of S. sclerotiorum in seed lots analyzed in comparison with the paper roll method; however, in comparison with Neon S method, despite its greater average, no significant differences were observed.